Students' interest and cognitive learning outcomes: Biology education in high schools during COVID-19 - Linda Gustia; S Suhartini (Biosfer: Jurnal Pendidikan Biologi, 2021)
The aim of this study to determine the interest in studying biology and the effect of interest in studying biology on the learning outcomes of cognitive biology during the Covid-19 pandemic. Based on several previous studies, it is known that online learning during the Covid-19 pandemic greatly influenced students' interest in learning biology. However, it is not yet known the level of interest in learning itself due to the effect of online learning, and it is not yet known the magnitude of the influence of interest in learning biology during online learning during the Covid-19 pandemic. This research was conducted in 2nd-grade science in Senior High School No. 13 Semarang using a survey method with correlational analysis. The data collection techniques in this study were questionnaires and documentation which were analyzed by testing the hypothesis using the correlation test and regression test. The results showed that the percentage of students' interest in learning biology online during the Covid-19 pandemic was 68.16%. The results of the correlation test show that there is a relationship between interest in learning biology with the cognitive biology learning outcomes of students. The results of the regression test and the value of R squared indicated that students' interest in learning biology affects learning outcomes of cognitive biology. The percentage of the influence of students' interest in learning biology on the cognitive biology learning outcomes is 34%. The interest in learning biology of students when learning biology online during the Covid-19 pandemic is still low. The interest in learning biology when learning biology online during the Covid-19 pandemic effect the cognitive biology learning outcomes of students